Written heritage of the Golden Horde - Dautov, Gumar F.; Gelyusya F. Kayumova, LiailiaI. Mingazova, Flera S. Sayfulina,; Yuldybaeva, Gulnar V. (Opción, 2019)
The article aims to consider the written heritage of the Golden Horde. This study’s methodological basis is the dialectical method of cognition of social and historicalliterature. Having analyzed the works by leading Turkic and Tatar poets of the Golden Horde such as Qutb, Kyatib, and many others, the authors stress that the Golden Horde created favorable opportunities for the development of literature, and the latter indeed flourished in that period. As a conclusion, the Golden Horde had a great impact on the formation of statehood and the spiritual life of the peoples living in Eurasia and partially North Africa.